Rethinking global digital health and AI-for-health innovation challenges. - Andrew Farlow; Alexander Hoffmann; Girmaw Abebe Tadesse; Deogratias Mzurikwao; Rob Beyer; Darlington Akogo; Eva Weicken; Tafadzwa Matika; MaryJane Ijeoma Nweje; Watu Wamae; Sako Arts; Thomas Wiegand; et al. (Public Library of Science (PLoS), 2023)
Digital health technologies can help tackle challenges in global public health. Digital and AI-for-Health Challenges, controlled events whose goal is to generate solutions to a given problem in a defined period of time, are one way of catalysing innovation. This article proposes an expanded investment framework for Global Health AI and digitalhealth Innovation that goes beyond traditional factors such as return on investment. Instead, we propose non monetary and non GDP metrics, such as Disability Adjusted Life Years or achievement of universal health coverage. Furthermore, we suggest a venture building approach around global health, which includes filtering of participants to reduce opportunity cost, close integration of implementation scientists and an incubator for the long-term development of ideas resulting from the challenge. Finally, we emphasize the need to strengthen human capital across a range of areas in local innovation, implementation-science, and in health services.